The three-dimensional organization of polyribosomes in intact human cells - Brandt, Florian; Carlson, Lars-Anders; Hartl, F. Ulrich; Baumeister, Wolfgang; Grünewald, Kay (Molecular cell, 2010)
Structural studies have provided detailed insights into different functional states of the ribosome and its interaction with factors involved in nascent peptide folding, processing, and targeting. However, how the translational machinery is organized spatially in native cellular environments is not yet well understood. Here we have mapped individual ribosomes in electron tomograms of intact human cells by template matching and determined the average structure of the ribosome in situ. Characteristic features of active ribosomes in the cellular environment were assigned to the tRNA channel, elongation factors, and additional densities near the peptide tunnel. Importantly, the relative spatial configuration of neighboring ribosomes in the cell is clearly nonrandom. The preferred configurations are specific for active polysomes and were largely abrogated in puromycin-treated control cells. The distinct neighbor orientations found in situ resemble configurations of bacterial polysomes in vitro, indicating a conserved supramolecular organization with implications for nascent polypeptide folding.